Pilot study MOVENDOP protocol - impact on quality of life following postoperative osteopathic abdominal mobilizations in patients operated for endometriosis - Aurélie Comptour; Caroline Dechambenoit; Fabrice Kwiatkowski; Astrid Vidal; Marie Duval; Marie De Antonio; Aurélie Jacobs; Nicolas Bourdel (PLoS ONE, 2025)
Background Surgery remains the gold standard for management of endometriosis, offering significant improvement in patient pelvic pain and quality of life (QoL). Postoperative tissue adhesions can however diminish these benefits, limiting the long-term effectiveness of the intervention. Despite the development of strategies and devices to reduce adhesion formation, their efficacy remains inconclusive. Objective This study aims to propose and evaluate a novel approach involving early visceral mobilization and training of patients in abdominal self-mobilization as a means to improve QoL following surgery. Methods This pilot study is a prospective, randomized, phase II superiority trial. Patients undergoing surgery for infiltrating endometriosis will be randomized, with a 2:1 ratio, into two groups. The intervention group (n = 42) will receive six sessions of osteopathic visceral mobilization with training in abdominal self-mobilization techniques, one preoperative, and five postoperative during the first month post-surgery. The control group (n = 21) will receive no osteopathic visceral mobilizations but will be offered an osteopathic session after one year. The primary endpoint is a minimum increase of 20 points (on a 100-point scale) in the Endometriosis Health Profile-30 (EHP-30) global score, at one year. Secondary endpoints include assessment of gastrointestinal quality of life (GIQLI), sexual function (FSFI), urinary symptoms (ICIQ-FLUTS), pain catastrophizing (PCS), as well as scar examination, pelvic pain, abdominal flexibility, use of medical and non-medical care, analgesic and hormonal treatments, pregnancy rate, physical activity, sedentary lifestyle and patient compliance. Statistical analyses will be based on a one-sided α=0.05 and β=0.15, assuming a standard deviation of 25 points in the EHP-30 global score. A total of 42 participants in the intervention group and 21 in the control group are required. Discussion This trial aims to demonstrate that early and repeated osteopathic sessions following surgery for endometriosis may significantly improve patient QoL.